CFD analysis of a pusher type reheating furnace and the billet heating characteristic. (25th March 2017) - Mayr, B.; Prieler, R.; Demuth, M.; Moderer, L.; Hochenauer, C.
Highlights: New method for the simulation of a pusher type reheating furnace in steady-state. The steel billets are modelled as a highly viscous fluid. Low calculation time compared to transient or iterative approaches. CFD simulation has been compared to measurements with reasonably close results. Abstract: In this study, a time saving method is presented for the simulation of an 18 MW pusher type reheating furnace with a production capacity of 60 t/h which is fired by natural gas burners. The periodic transient reheating of the billets and the gas phase combustion was calculated in one steady state calculation. This is possible due to the special configuration of the furnace where the billets are placed side by side. Therefore, the steel billets are treated as a fluid with a high viscosity. The results of the gas phase simulation were validated with measurements from the control system of the furnace, and showed a good agreement with an averaged deviation of 38 K. The calculated billet temperature were compared to measurements and showed with a deviation of 27 K also a good agreement. Additionally, the temperature of the billets was also calculated with a numerically efficient iterative approach. The two approaches showed close agreement and similar trends for the temperature distribution in the billets. Which was also verified by measurements from a thermographic camera. This proves the applicability of this method for this type of furnaces which can be used for optimisation with low calculation time.